Development of Iron Sequester Antioxidant Quercetin@ZnO Nanoparticles with Photoprotective Effects on UVA-Irradiated HaCaT Cells. (26th August 2021) - Nisar, Muhammad Farrukh; Yousaf, Maryam; Saleem, Muhammad; Khalid, Hamad; Niaz, Kamal; Yaqub, Mustansara; Waqas, Muhammad Yasir; Ahmed, Arsalan; Abaid-Ullah, Muhammad; Chen, Jinyin; Chen, Chuying; Rengasamy, Kannan R. R.; et al.
Abstract : Background . Solar ultraviolet radiation A (UVA, 320-400 nm) is a significant risk factor leading to various human skin conditions such as premature aging or photoaging. This condition is enhanced by UVA-mediated iron release from cellular iron proteins affecting huge populations across the globe. Purpose . Quercetin-loaded zinc oxide nanoparticles (quercetin@ZnO NPs) were prepared to examine its cellular iron sequestration ability to prevent the production of reactive oxygen species (ROS) and inflammatory responses in HaCaT cells. Methods . Quercetin@ZnO NPs were synthesized through a homogenous precipitation method, and the functional groups were characterized by Fourier transform infrared (FTIR) spectroscopy, whereas scanning electron microscopy (SEM) described the morphologies of NPs. MTT and qRT-PCR assays were used to examine cell viability and the expression levels of various inflammatory cytokines. The cyclic voltammetry (CV) was employed to evaluate the redox potential of quercetin-Fe 3+ /quercetin-Fe 2+ complexes. Results . The material characterization results supported the loading of quercetin molecules on ZnO NPs. The CV and redox potential assays gave Fe-binding capability of quercetin at 0.15 mM and 0.3 mM of Fe(NO3 )3 . Cytotoxicity assays using quercetin@ZnO NPs with human HaCaT cells showed no cytotoxic effects and help regain cell viability loss following UVA (150 kJ/m 2 ). Conclusion . Quercetin@ZnO NPs showed that efficient quercetin release action is UV-controlled, and the released quercetin molecules have excellent antioxidant, anti-inflammatory, and iron sequestration potential. Quercetin@ZnO NPs have superior biocompatibility to provide UVA protection and medication at once for antiphotoaging therapeutics.